The phantom virus : an unofficial novel - Cheverton, Mark (Cheverton, Mark. Herobrine's revenge, 2016)
"Herobrine, the artificially intelligent virus, was deleted. The computer it resided in was completely destroyed. Without their leader, the few survivors of its evil army were cast away into the shadows. It looked as if there would finally be peace and happiness throughout the servers of Minecraft. But suddenly, and mysteriously, software began misbehaving. Sheep fell from the sky. Snowballs appeared out of nowhere. What seemed at first like harmless glitches quickly became dangerous. Pigs begin walking backwards, it starts to snow in the middle of the desert, and sheep are falling from the sky. Gameknight999, the User-that-is-not-a-user, has no choice but to investigate. But the odd yet harmless pranks are turning deadly, and it's not long before entire villages are completely destroyed. Examining the arrogant clues, Gameknight is no longer so sure that Herobrine was destroyed after all. Is it possible he escaped? Everything points towards a deadly trap far worse than anything that Minecraft has seen before. Will Gameknight solve the puzzle before the Overworld is destroyed?"--Amazon.com.